EKSPLORASI KEMBAR MAYANG JANUR PENGANTIN ADAT JAWA PADA PEMBELAJARAN MATERI BANGUN DATAR - Dwi Anjani, Rizka; Marsha Anindya, Faisa; Tri Maesaroh, Atika (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
Ethnomathematics is a form of mathematics influenced by culture as a contextual form. Kembar Mayang is one of the ethnomathematical elements that can provide visual images in real life. The method used in this study is a descriptive qualitative method with an ethnographic approach. Observation and documentation were used to identify ethnomathematics in the Kembar Mayang ornaments. In comparison, literature is used to discover the cultural values in Mayang ornaments more deeply. The result of this study is that there are mathematical elements (ethnomathematics) in the ornaments of Kembar Mayang. Through observing Kembar Mayang ornaments in mathematics learning with an ethnomathematical approach, it is explained that cultural elements can be used in mathematics learning.